БЎЛАЖАК ЎҚИТУВЧИЛАР МАЪНАВИЯТИНИ ШАКЛЛАНТИРИШ МЕЗОНЛАРИ ВА КЎРСАТКИЧЛАРИ - Утанов, У. (SCIENCE and SOCIETY, 2017)
The article deals with the issues of spiritual education, the criterias and indicators of forming spirituality in future teachers. The article also contains the review of scintific research works on the issue under discussion.
Keywords: criteria; pedagogical criterias; spiritual criterias; historical method; logicality; generalization; psychological; communicative; spiritual analysis; spiritual need; indicator